2021
DOI: 10.2147/cmar.s295368
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Genomic Instability in Cerebrospinal Fluid in Patients with Meningeal Metastasis

Abstract: This study aimed to explore the genomic instability in cerebrospinal fluid (CSF) in patients with meningeal metastasis (MM). Material and Methods: We collected the blood and CSF samples of 15 MM patients and one brain parenchymal metastasis (BPM) patient. A panel of 543 cancer-related genes was conducted to analyze the status of genomic instability in CSF and plasma cellfree DNA (cfDNA) of all patients. Subsequently, nine patients underwent low-depth whole-genome sequencing (WGS) analysis to verify the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Aneuploidy, another trigger of genomic instability, is also widely detected in patients in CSF from LM patients. 42 The coexistence of genomic instability and aneuploidy could promote each other and lock in a vicious cycle, leading to genomic copy number changes. The CNVs facilitate tumor cells to acquire phenotypes to survive under selective pressure such as anti‐cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aneuploidy, another trigger of genomic instability, is also widely detected in patients in CSF from LM patients. 42 The coexistence of genomic instability and aneuploidy could promote each other and lock in a vicious cycle, leading to genomic copy number changes. The CNVs facilitate tumor cells to acquire phenotypes to survive under selective pressure such as anti‐cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 LOH uniquely occurred in CSF rather than plasma, accompanied by more genomic mutations and CNVs. Aneuploidy, another trigger of genomic instability, is also widely detected in patients in CSF from LM patients 42 . The coexistence of genomic instability and aneuploidy could promote each other and lock in a vicious cycle, leading to genomic copy number changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, until our study last year, few studies specifically examining GI in patients with MM had been conducted [ 14 ]. Normally, the GI status is analyzed using genomic DNA samples from tumor tissues rather than cell-free circulating tumor DNA (ctDNA) extracted from plasma, though, in many cases, cfDNA has been used as a surrogate reflecting the genomic profile of solid tumors for concomitant diagnosis, minimal residual disease (MRD) surveillance, and the identification of drug resistance mechanisms [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…CSF is a circulating fluid unique to the central nervous system, filling the ventricles and spinal cord, that comes into direct contact with tumor cells at intracranial lesions and is expected to be a breakthrough point for the liquid biopsy of brain tumors [ 18 , 19 , 20 ]. In our previous study, we found that the GI status in the MM of multiple solid tumors could be analyzed using CSF cfDNA [ 14 ]. In the present study, we established a GI score relying on high-throughput genetic testing to describe the GI status in CSF cfDNA and assess its clinical significance as a prognostic indicator in solid tumor patients with MM.…”
Section: Introductionmentioning
confidence: 99%